ANALYSIS OF THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE BASED ON ASEAN CORPORATE GOVERNANCE SCORECARD: CASE STUDY PT JAKARTA PROPERTINDO (PERSERODA) - Ferry Richard Hamonangan; Ancella A. Hermawan (Dinasti Publisher, 2020)
So far, a lot of research has seen the implementation of Good Corporate Governance (GCG) in private companies. Like SOEs, Regionally Owned Enterprises (BUMD), although running the same business as private companies, have different characteristics that can cause Agency Problems that can harm stakeholders. This study aims to analyze the quality of GCG implementation at PT Jakarta Propertindo (Perseroda), a BUMD owned by the Provincial Government of DKI Jakarta, using a scoring approach from the ASEAN Corporate Governance Scorecard. This study only uses criteria in the ASEAN Corporate Governance Scorecard that can be used to measure a BUMD. This is because the characteristics of BUMD are not exactly the same as pure private companies. The results indicate that PT Jakarta Propertindo (Perseroda) has not fully met all the GCG principles contained in the ASEAN Corporate Governance Scorecard.